Pattern of Dyslipidemias, Associated Atherogenic Risk and Insulin Sensitivity in Type 2 Diabetes Mellitus (Western Journal of Medical and Biomedical Sciences, 2025)
Dyslipidemia is a major phenotype associated with diabetes mellitus, and this is essential in the development of cardiovascular risk. This study aimed to establish the most common dyslipidemia pattern among type 2 DM, atherogenicity, and associated insulin sensitivity. Across-sectional study, involving 141 type 2 diabetes patients and 140 healthy individuals as controls, was adopted. A multistage sampling technique was employed, and a semi-structured interviewer-administered questionnaire was used to collect socio-demographic and clinical data. The combined dyslipidemia pattern had the highest percentage among subjects, with a value of 52(45.6%) observed. It was followed by mixed dyslipidemias with a value of 50(43.9%). Ahigher percentage of increased risk of CVD was found among the subjects for CRI-I (74; 52%), CRI-II (73; 51.8%), and AC (75; 53.2%) compared with control CRI-I (15; 10.7%), CRI-II (7; 5.0%) and AC (15; 10.7%), p-values
Keywords: Atherogenic indices; Dyslipidemias; HbA1C; HOMA-IR; Insulin resistance; QUICKI